Foreign Language Teachers’ Perceptions after Gamified Classroom Practice - Jaume Batlle; Vicenta González (Colombian Applied Linguistics Journal)
This study examines the perceptions and beliefs of thirteen teachers of foreign languages who have received specialized training in gamification and have put it into practice in the classroom. Specifically, the study analyses the impact of gamification in the three years following its introduction into their teaching practices. To gain insights into teachers’ perspectives and attitudes towards gamification, thirteen semi-structured interviews were conducted. The analysis of the interviews revealed that gamification is viewed by teachers as a motivating and collaborative strategy which can be challenging to implement in some courses but can be facilitated by certain key elements such as the use of narratives in the classroom. Additionally, teachers highlighted the need for more training in this new pedagogical strategy and the importance of collaborative planning of gamified experiences with colleagues. The value of this study lies in showing the impact of gamification on the perceptions of foreign language teachers in the medium term after its introduction into their classrooms.